Hypertension and the Kidney: Reduced Kidney Mass Is Bad for Both Normotensive and Hypertensive Rats. (28th June 2021) - Ware, Kyle; Yildiz, Vedat; Xiao, Min; Medipally, Ajay; Hemminger, Jessica; Scarl, Rachel; Satoskar, Anjali A; Hebert, Lee; Ivanov, Iouri; Biederman, Laura; Brodsky, Sergey V
Abstract: BACKGROUND: Hypertension is a leading cause of chronic kidney disease worldwide. Early studies demonstrated the short-term effects of hypertension on kidney function and morphology in ablative nephropathy. The aim of this study was to investigate the long-term consequences of hypertension in 5/6 nephrectomy (5/6NE) model. METHODS: Reduction of the kidney mass by 5/6NE was created in spontaneous hypertensive rats (SHR) and genetically similar normotensive Wistar Kyoto (WKY) rats. Blood pressure, serum creatinine (SCr), hematuria, and proteinuria were monitored weekly for 23 weeks. Kidney morphology was assessed at the end of the study. Sham-operated rats from both strains were used as controls. RESULTS: Rats with 5/6NE had increased SCr, blood pressure, hematuria, and proteinuria in both SHR and WKY. Even though the SCr levels and blood pressure were greater in 5/6NE SHR as compared with 5/6NE WKY rats, absolute changes from sham-operated rats were not statistically significant between these 2 groups. 5/6NE SHR had earlier onset and higher proteinuria than 5/6NE WKY rats. Hematuria was similar in 5/6NE SHR and 5/6NE WKY rats. However, 5/6NE SHR had enlarged glomeruli, increased interstitial fibrosis, and prominent intimal thickening in the small arteries/arterioles as compared with 5/6NE WKY rats. CONCLUSIONS: The long-term severity of kidney injury correlated with higher blood pressure. Reduction of the kidney mass increases SCr, hematuria, proteinuria, and blood pressure in both normotensive and hypertensive rats. Histological assessment provides better information about underlying chronic kidney injury than actual changes in SCr and urinalysis.